Implementation of Augmented Reality with Marker Based Tracking on Custom Gift Products by Tricksy.co - Raisa Mutia Thahir; Jasmine Aulia Mumtaz; Kinaya Khairunnisa Komariansyah; Wien Kuntari (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
This research explores the integration of Augmented Reality (AR) technology into custom gift products by Tricksy.co to create a more interactive and personalized gift-giving experience. By utilizing EyeJack Creator, a platform for creating AR photo markers, the system allows customers to design gifts that display personalized videos when scanned. The process includes generating AR markers, integrating QR codes, and ensuring compatibility with both iOS and Android devices. System testing confirmed that the AR markers successfully displayed the videos as intended, with smooth functionality across different platforms. However, slow internet connections impacted the speed of AR content downloading. This study highlights the potential of AR to revolutionize the gift industry by adding a unique digital layer to physical gifts, offering both emotional and interactive value.